Telitacicept as an alternative to non-steroidal immunosuppressive therapies in the treatment of myasthenia gravis: a study on clinical efficacy and steroid-sparing effect - Fang, Zheyu; Zhang, Yuan; Zhang, Yu; Zhang, Qiaoyi; Qu, Xi; Pan, Shengli; Wan, Bingbing; Yang, Shiyin; Zhang, Xu; Li, Jia (Frontiers in Immunology, 2025)
IntroductionMyasthenia Gravis (MG) is an autoimmune disorder characterized by impaired neuromuscular junction (NMJ) transmission. Current treatments for MG include steroids and nonsteroidal immunosuppressive therapies (NSISTs). However, approximately 20% of patients show a poor response to these therapies, which are often associated with significant side effects. Telitacicept, a novel recombinant fusion protein targeting the BAFF/APRIL pathway, has shown promise in treating autoimmune diseases, including MG.MethodsThis retrospective study compared the efficacy of telitacicept monotherapy (10 patients) to NSISTs (16 patients) and sequential therapy (6 patients) in managing Myasthenia Gravis (MG) at The First Affiliated Hospital of Wenzhou Medical University (July 2020-November 2024). The primary endpoint was the time to achieve minimal symptom expression (MSE), and secondary endpoint was the change in the mean daily prednisone dosage from baseline to month 4.ResultsAmong telitacicept-treated patients, 80% achieved MSE within 4 months, with a significant reduction in mean daily dose of prednisone (from 45.00 mg to 6.25 mg, P < 0.001). In contrast, only 12.5% of the NSISTs group achieved MSE, with no significant change in mean daily dose of prednisone (P = 0.091). The sequential therapy group (efgartigimod followed by telitacicept) maintained stable disease conditions.ConclusionTelitacicept is effective in inducing MSE rapidly and offers a steroid-sparing effect, making it a promising alternative to traditional NSISTs with fewer side effects in MG patients.